Earning Per Share as a Market Perfomance Measure in Increasing Stock Returns of Pharmaceutical Companies - Tahlis Ayu Fatmawati; Ana Kadarningsih (International Journal of Economics, Management and Accounting, 2024)
Stock prices serve as a benchmark for investors to assess a company's success. A positive stock return is an indicator of business success for a company. This study has three main objectives: to examine the influence of Earnings Per Share (EPS) on stock returns, to investigate the relationship between Return On Assets (ROA) and stock returns, and to determine the extent to which the Debt to Equity Ratio (DER) affects stock returns. The population of this study consists of 11 pharmaceutical companies listed on the Indonesia Stock Exchange during the period of 2018-2023. Simple random sampling was used to randomly select samples from the population, resulting in 264 quarterly financial data samples. The type of data used in this study is quantitative data obtained from semi-annual reports downloaded from www.idx.co.id and from the respective pharmaceutical companies' websites. Data analysis was conducted using Eviews version 10. The study found that only one variable, Earnings Per Share (EPS), significantly influences stock returns. The other two variables, Return On Assets (ROA) and Debt to Equity Ratio (DER), do not have a significant effect on stock returns.